2016
DOI: 10.1111/wrr.12493
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble urokinase‐type plasminogen activator receptor as a serum marker of inflammatory response that leads to tissue damage and surgical complication

Abstract: Unrestrained activation of the proteolytic systems in anastomotic tissue during repair has been implicated in the pathogenesis of anastomotic leakage. We hypothesized that this mechanism may promote an up-regulation of the urokinase-type plasminogen activator system and a spillover of soluble urokinase-type plasminogen activator receptor (suPAR) into blood. In this retrospective analysis patients with anastomotic leakage were compared with a group of matched uncomplicated patients. Anastomotic leakage complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The present study clearly suggests that perioperative circulating suPAR levels remain stable and are not affected by general anesthesia and/or the surgical stress response. A similar stability has also been reported in smaller cohorts, including patients undergoing elective coronary bypass graft surgery under cardiopulmonary bypass, septic surgical patients with bloodstream infection, and patients with anastomotic leakage after elective colorectal surgery [20-22]. The present study includes a larger sample and various types of major non-cardiac surgery, highlighting the utility of suPAR in advanced perioperative management and planning.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study clearly suggests that perioperative circulating suPAR levels remain stable and are not affected by general anesthesia and/or the surgical stress response. A similar stability has also been reported in smaller cohorts, including patients undergoing elective coronary bypass graft surgery under cardiopulmonary bypass, septic surgical patients with bloodstream infection, and patients with anastomotic leakage after elective colorectal surgery [20-22]. The present study includes a larger sample and various types of major non-cardiac surgery, highlighting the utility of suPAR in advanced perioperative management and planning.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, perioperative suPAR levels remain stable. Adding suPAR measurements to existing blood test panels and/or risk scores may allow further stratification of preoperative inflammation and perioperative risk [4, 9, 19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…suPAR is a stable biomarker of low‐grade inflammation, associated with development and presence of various diseases, and has shown to provide prognostic value as a biomarker in acute medical patients [14, 15, 17, 20, 21]. It has been shown that the predictive value of suPAR is present years before the development of disease, and suPAR is stable during an early inflammatory state and surgical trauma [41, 42]. These properties could benefit the preoperative risk assessment by reflecting the overall inflammatory state of the patient, independent of the underlying pathologies or reasons for surgery.…”
Section: Discussionmentioning
confidence: 99%